The Legal and Ethical Implications of Surveillance in Criminal Law: A Literatur Review - Cindrapole, Andi Cakra; Rosmini, Siti (eScience Humanity Journal, 2024)
This study investigates the legal and ethical implications of the use of surveillance technology in criminal law through a comprehensive literature review. With the increasing capacity of technologies such as CCTV, digital surveillance, and the use of big data, important questions arise regarding the balance between security and personal rights. The study analyzes a variety of sources from journal articles, court rulings, and policy documents to identify key issues faced by legal practitioners and policymakers. The results of this review show that there is an intense debate between the need for security and the protection of individual privacy. The study also explores how different jurisdictions are responding to these challenges and proposes a framework to ensure that the use of surveillance technology remains accountable and transparent. This literature review aims to provide in-depth insight into the emerging complexities at the intersection of technology, ethics, and criminal law, while offering guidance for legal professionals in formulating ethical and effective strategies for addressing crime.